Characterization of Meiothermus taiwanensis Galactokinase and its Use in the One‐Pot Enzymatic Synthesis of Uridine Diphosphate‐Galactose and the Chemoenzymatic Synthesis of the Carbohydrate Antigen Stage Specific Embryonic Antigen‐3. Issue 14 (1st August 2014) - Li, Si‐Peng; Hsiao, Wei‐Chen; Yu, Ching‐Ching; Chien, Wei‐Ting; Lin, Hong‐Jyune; Huang, Li‐De; Lin, Chien‐Hung; Wu, Wan‐Ling; Wu, Shih‐Hsiung; Lin, Chun‐Cheng
Abstract Herein, we report the first characterization of a novel galactokinase from Meiothermus taiwanensis sp. nov. WR‐220 (MtGalK), which is overexpressed in E. coli and exhibits a kcat/Km value of 168.47 mM−1 s−1 toward Gal at 75 °C. The thermophilic MtGalK shows specific substrate recognition toward the Gal configuration with limited tolerance for modifications at the C‐2 position to form products such as GalN‐1‐P, GalN3‐1‐P, and GalNAc‐1‐P. Due to its unique thermostability toward elevated reaction temperatures, MtGalK served as an ideal biocatalyst in the synthesis of useful sugar‐1‐phosphates and was further combined with glucose‐1‐phosphate thymidylyltransferase (RmlA) and α‐1, 4‐galactosyltransferase (LgtC) to achieve the efficient preparative‐scale synthesis of globotriose analogs (Gb3) using a one‐pot three‐enzyme system. In combination with a chemical synthetic strategy, a carbohydrate antigen from breast cancer stem cells, stage specific embryonic antigen‐3 (SSEA‐3) pentasaccharide, was synthesized from Gb3 in ten steps with a 23% overall yield. This flexible chemoenzymatic strategy for the synthesis of SSEA‐3 also allowed us to further expand the inventory of valuable natural and non‐natural glycans. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>